2014
DOI: 10.1177/0022034514527288
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Tissue Transcriptomes Identify Distinct Periodontitis Phenotypes

Abstract: The currently recognized principal forms of periodontitischronic and aggressive-lack an unequivocal, pathobiologybased foundation. We explored whether gingival tissue transcriptomes can serve as the basis for an alternative classification of periodontitis. We used cross-sectional wholegenome gene expression data from 241 gingival tissue biopsies obtained from sites with periodontal pathology in 120 systemically healthy nonsmokers with periodontitis, with available data on clinical periodontal status, subgingiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 27 publications
6
111
0
Order By: Relevance
“…22 Biochemical analyses demonstrated a strong regulatory activity on B cell receptor (BCR) signaling. Similar to the results we have obtained, Kebschull et al 23 , Demmer et al 18 and Davanian et al 23 stated the upregulation of FCRL5 gene. In this context, overexpression of FCRL5 supports the findings of other studies in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…22 Biochemical analyses demonstrated a strong regulatory activity on B cell receptor (BCR) signaling. Similar to the results we have obtained, Kebschull et al 23 , Demmer et al 18 and Davanian et al 23 stated the upregulation of FCRL5 gene. In this context, overexpression of FCRL5 supports the findings of other studies in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Kebschull et al 23 performed whole genome transcriptome analysis on 241 gingival tissues with periodontitis and 120 gingival tissues of healthy individuals. As a result, they determined upregulation of MZB1 gene similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus according to the present pilot study we cannot conclude that there is a vascular impairment in gingiva in smokers even though we found some differences in vascular parameters. The clinical classifications of the periodontitis tend not to be correlated to tissue and molecular reactions (24) and call for the setup of a new biologically based model for the classification of periodontal disease. Using one of these novel molecular methods to correlate the vascular reactivity to the severity of the disease may answer this question in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identified MRs may be involved either in the transition from states of gingival health to periodontitis or in the maintenance of a state of established periodontal pathology. However, note that in our previous work that examined sequential gene activation during the induction and resolution of experimental gingivitis in an independent Master regulators whose regulons were significantly enriched (per Fisher's exact test) for the 586 genes identified as being potentially relevant for the distinction between 2 clusters of patients based on transcriptomes of periodontitis-affected tissues (Kebschull et al 2014). BH, Benjamini-Hochberg adjusted P value; OR, odds ratio.…”
Section: Figure To Identify Master Regulator (Mr) Genes Marina (Masmentioning
confidence: 99%
“…We demonstrated that distinct patterns of subgingival microbial colonization associate with discernible gene expression signatures in the adjacent gingival 653588J DRXXX10.1177/0022034516653588Journal of Dental ResearchMaster Regulator Genes in Human Periodontitis research-article2016 tissues (Papapanou et al 2009). Despite limited molecular differences among lesions from chronic or aggressive periodontitis (Kebschull et al 2013), gingival tissue transcriptomes identified 2 clusters of patients (Kebschull et al 2014) who differed with respect to periodontitis extent and severity, levels of specific subgingival microbiota, and serum IgG antibody responses to selected bacteria.…”
Section: Introductionmentioning
confidence: 99%